HOMILI MELAMPAUI SEGALA BENTUK KATEKESE (Evangelii Gaudium, art 135-159) - Marianus Dinata Alnija (Jurnal Filsafat dan Teologi Katolik, 2019)
Today Christians has faced various challengge that plunge many christian into consumerism, terrible sadness, hedonism and covetous. As the result many christian become selfish, irritable, and egoist. For that reason, Pope Francis urged many preachers should work hard in proclaiming the gospel especially through homilies because homilies beyond all form of catechesis. This paper aims to explore Pope Francis' theological ideas about concerning homily. In a way of exploring the theological conception regarding homily, the writer treats the apostolic exhortation of evangelii Gaudium article number 135-159.